Dag yig gnad cheʼi tshig bsdus la don rgyas pa dri med me loṅ źes bya ba bźugs so - Saṅs-rgyas-bstan-ʼdzin, Gser Dgon, 1924-1990 (s.n., 1970)
Orthographical dictionary of literary Tibetan, in verse with prose annotations.